Liquid chromatography-tandem mass spectrometry analysis of 17-hydroxyprogesterone in dried blood spots revealed matrix effect on immunoassay - Han, Liqiao; Tavakoli, Norma P.; Morrissey, Mark; Spink, David C.; Cao, Zhimin (Tim) (Analytical and bioanalytical chemistry, 2019)
Immunoassays for measuring 17-hydroxyprogesterone (17-OHP) produce high rates of false positives that impact the identification of congenital adrenal hyperplasia (CAH) in neonates. A confirmatory test with high analytical specificity employing liquid chromatography-tandem mass spectrometry (LC-MS/MS) methodology is needed in newborn screening for CAH. 17-OHP and cortisol were extracted from dried blood spot (DBS) samples, resolved on a C18 column, and measured using tandem mass spectrometry. The results were compared with those determined using the AutoDELFIA immunoassay. The LC-MS/MS method had a limit of quantitation of 10.0 and 5.0 ng/mL for 17-OHP and cortisol, respectively. The method characteristics showed coefficient variation (%CV) ≤ 11.9% for both 17-OHP and cortisol, recoveries ranging from 83.1 to 101.5% for 17-OHP and from 95.1 to 102.8% for cortisol, and linearity with R 2 = 0.9994 for 17-OHP and R 2 = 0.9996 for cortisol, clinical sensitivity of 100.0% and a specificity of 96.4% as obtained by receiver operating characteristic analysis on 45 patient samples when 17-OHP > 39.1 ng/mL was selected as the cutoff value. Comparison between the LC-MS/MS and the AutoDELFIA immunoassay methods revealed a poor correlation for patient DBS samples ( R 2 = 0.6784); however, an excellent correlation was obtained for QC and proficiency test (PT) DBS samples ( R 2 = 0.9797). The LC-MS/MS method produced reliable results for 17-OHP and cortisol for the diagnosis of CAH. The AutoDELFIA immunoassay appears to be subject to matrix effects in the analysis for 17-OHP in DBS patient samples. The DBS samples of non-patient origin may not be suitable for assessing analytical accuracy of immunoassays.